IMPLEMENTATION OF GUIDED INQUIRY MODELS IN REDOX MATTER TO TRAIN STUDENTS CRITICAL THINKING WITH BACKGROUND COGNITIVE STYLE FIELD INDEPENDENT AND FIELD DEPENDENT (Universitas Negeri Surabaya, 2017)
This study aims to observe the implementation, student activity, increased of students critical thinking after this models implemented in 37 student with Field Independent and Field Dependent cognitive style. Type of this study is quantitative descriptive research. Target of this research is student of X MIA 5 in SMAN 11 Surabaya with research design one group pretest-posttest. Instrument used in this research is observation of feasibility Guided Inquiry models sheets; observation student activity sheets; and critical thinking skills test sheets. Based on result of this research and discussion, so (1) feasibility of Guided Inquiry models for trained critical thinking skills student has average value at first meeting and second meeting is 3.8; and 3.85 in criteria very good; (2) based on percentage of student activity time, which showed student train critical thinking skills for Field Independent student as much as 43.03% (first meeting) and 44.48% (second meeting) also for student with Field Dependent as much as 38.3% (first meeting) and 40.6% (second meeting); (3) increased of critical thinking skills in high category for student Field Independent as much as 56% and 0% for student Field Dependent, in medium category for student Field Independent as much as 41% and 40% for student Field Dependent, in low category for student Field Independent as much as 3% and 60% for student Field Dependent Keywords: Guided Inquiry, Criticall Thinking Skills, Cognitive style, and Redox